Representation of Political Messages of the Millennial Generation in the E-Talk Show Program on TV One - Wasilah, Nur; Latief, Rahmawati; Hatta, Harmin (Jurnal Mercusuar, 2021)
This research aims to analyze the denotation, connotation, and myth in text and images and to understand the representation of political messages of the millennial generation in the TV One E-Talk Show episode "Political Awareness: Millennial Nowadays." This research uses descriptive qualitative research with Roland Barthes’ semiotics model. The data collection method used is documentation techniques and information tracing from various sources. The results of the study indicate that the meaning conveyed in the program is that millennials have a high spirit to obtain justice, recognition, and identity in society. Second, the democracy index decreases because the dominant society’s criticism is ignored. Third, student demonstrations are activities that occur every year. Fourth, power is identical to politics. Fifth, a person who is raised in a political family environment tends to work in the political field. Meanwhile, the representation of political messages of the millennial generation in this program is not separated from a dominant ideology, namely media power as one of the factors shaping public awareness represented through Sherly Annavita and Hillary Brigitta as millennials and speakers in the episode.